KONSTRUKSI SOSIAL TRADISI MANGGILIANG GHOMPAH PADA ACARA PERKAWINAN DI KECAMATAN CERENTI KABUPATEN KUANTAN SINGINGI PROVINSI RIAU - ", Noviandri; Salam, Noor Efni (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Manggiliang ghompah is a tradition of cooking a mutual to prepare the meal of food in the event of marriage society Sub Cerenti Kuantan Singingi Regency of Riau Province which is currently still being done in the marriage of the local community, the purpose of this research study focuses on sight, enthusiasm as well as a deeper meaning towards the tradition of Manggiliang ghompah in the perspective of social construction.This type of research is qualitative research with approach of Phenomenology. Data collection techniques using observation and in-depth interview with 8 persons specified in Informant purposive sampling accompanied documentation field. To affirm the validity of research data is made through an extension of the participation and the triangulation of the data.The results of this research show the process of externalization of the community in view of the development of the case of the manggiliang tradition Cerenti ghompah who no longer classify the community into the future then as matrilineal tribe, then Manggiliang ghompah tradition that objectification is exposed to a new culture that is cattering, then shift the tool and entertainment that is used on the ghompah manggiliang tradition has changed, as well as the internalization of society Cerenti in interpret the presence of these manggiliang ghompah tradition.Keywords: Social Construction of Reality, Manggiliang Ghompah, Cerenti